Evaluation of losses of Kam’yanets’ – Podil’skiy as a result of the harmful emissions by motor transport - Honchar, Lyudmyla; Shpintal, Mykhailo; Kushnir, Oksana (Видавництво Львівської політехніки, 2010)
The method of calculation of the emissions of contaminating matters into the air by transport vehicles was researched in the article. The evaluation of losses made to the environment by harmful matters and greenhouse gases of motor transport of Kam'yanets' - Podil'skiy was conducted.
Keywords: contamination by motor transport; method of calculation of the emissions; algorithm of calculation of losses; evaluation of losses